A contextual and intertextual reading of Psalm 118 - Prinsloo, G. T. M. (Old Testament Essays, 2003)
It is a sine qua non of biblical scholarship that texts should never be interpreted in isolation. Curiously enough ever since the rise of critical biblical scholarship this key aspect of the exegetical process has been largely ignored in the exegesis of the Book of Psalms. Nowhere is this shortcoming better illustrated than in the arbitrary allocation of a social and historical background to virtually any psalm. In this paper the shortcomings of this atomistic approach is illustrated by referring to a specific psalm, namely Psalm 118. A short overview of various interpretational perspectives on Psalm 118 in commentaries and other studies is given. It is argued that a contextual and intertextual reading of Psalm 118 will act as a counterbalance to arbitrary decisions on the interpretation of the psalm. It is the interplay between intra- and intertextual data that guides the exegete towards reconstructing an extratextual context for the poem.
free